Influence of articular arthroscopy-like washout on fracture healing of intra-articular fractures; animal experiment - Orman, Osman; Ozturk, Kahraman; Baydar, Mehmet; Guneren, Ethem; Taslidere, Elif; Orman, Mujgan; Ozel, Omer (EXPERIMENTAL BIOMEDICAL RESEARCH, 2020)
Aim: To examine whether the application of intra-articular lavage during arthroscopic joint fracture surgery can disturb fracture union and cartilage healing. Metods: Twenty New Zealand rabbits were then randomly divided into 3 groups; these groups consisted of 2 surgical groups including eight rabbits and a control group consisting of 4 rabbits. After both rear limbs exposed with a medial parapatellar incision, medial femoral condyle was fractured. Four groups were created by doing anatomic reduction or non-anatomic reduction and making irrigation or no irrigation. (Group 1: Fixed by creating a gap and no Irrigation; Group 2: Fixed by creating a gap and irrigation; Group 3: Fixed with complete reduction and no irrigation; Group 4: Fixed with complete reduction and irrigation) X-rays of both knees of all rabbits were taken at the end of the second week and at the end of the eighth week. The operated knees were collected for histopathological analysis. Results: Radiological data show a significant difference in the level of ossification between the groups in the 2nd week; however, this difference was lost in the 8th week. Histopathologically, at the end of week 8, it was observed that the subchondral bone tissue was incompletely renewed in all the groups. The cartilage tissue of the joint surface was not fully formed and renewed and that it did not completely coalesce with the old cartilage tissue in all of the groups. Compared with the other groups, the group that fracture was anatomically reducted with no irrigation (Group 1), the cartilaginous tissue layer formed was thicker while the surface of the tissue was flatter. Conclusion: There were no adverse effects of intra-articular lavage on fracture union and cartilage healing in an in vivo environment. Nonetheless, the findings of this study should be confirmed with a larger sample size.